(3NdGUI GdOdGFd aj JfbjM GdeSGFds - (3GHf ecj , Ydj Hf CMeO Hf ecj GdQGRj, MSGe GdOjf CHh GdMSf,J (B598 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh GdMSf Ydi Hf CMeO GHf eci GdMeO ddg Gdehab ddUhGH hHYO aEf GdbdhH hGdWHGY de JRd eGFdI Edi EONGQ GdPcQ GdLejd hCSeMJ HGdEQaGb hGdEQaGO def Tci s
(3BNQgG (B:s
(3hddRhL ef GdeSFdI GdKGfjI SHYI CSge hbOQg ef GdOQge MHI hfUa MHg , hYdi gPG GdbjGS GdfXGFQ Ef TGA Gddg JYGdi bO Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HChdgG agQS ddeNWhWs
(3cJHJ YfGhjjf GdCHhGH HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B256 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B30 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B703s
Keywords: (3Gdabg GdESdGejs